Taxonomy of the genus Phymatura J. Sahlberg (Coleoptera: Staphylinidae: Aleocharinae) in the Korean Peninsula - Kim, Yoon-Ho; Ahn, Kee-Jeong (Zootaxa, 2016)
A taxonomic study of Korean Phymatura J. Sahlberg is presented. Three species are recognized, one of which, P. bigranipennis (Bernhauer) comb. nov., is transferred from the genus Atheta Thomson. Pseudatheta gonggaensis (Pace) is restored to the genus Phymatura. Phymatura bigranipennis and P. gonggaensis are identified for the first time in the Korean Peninsula. A key, redescriptions and illustrations of diagnostic characters are provided.